Wearable Integrated Soft Haptics in a Prosthetic Socket - Barontini, Federica; Catalano, Manuel G.; Grioli, Giorgio; Bianchi, Matteo; Bicchi, Antonio (IEEE robotics and automation letters, 2021)
Modern active prostheses can be used to recover part of the motor function associated with the loss of a hand. Nevertheless, most sensory abilities are lost, and the person has to manage interaction by relying mostly on visual feedback. Despite intensive research devoted to convey touch related cues, very few solutions have been integrated in a real prosthesis worn by a user. This letter describes a soft pneumatic feedback system designed with integrability and wearability among its main concerns. At the system core, two soft pneumatic actuators are placed in contact with the subject's skin and inflated to provide pressure stimuli, which can be used to represent force exerted by the hand grasping. We report on the design and the characterization of the system, including behavioural experiments with able-bodied participants and one prosthesis user. Results from psychophysical, dexterity and usability tests show that the system has the potential to restore sensory feedback in hand amputees, and can be a useful tool for enabling a correct modulation of the force during grasping and manipulation tasks.